Nilai-Nilai Ketauhidan: Telaah Strategi Pembelajaran Bahasa Arab Berbasis Ilmu Tauhid - Aisha Nurul Azkia; Andini Br Sembiring; Aulia Nazwa Panjaitan; Bela Wahyuni Manurung; Juliana Juliana; Laila Attiyah Ramadhani Sitorus; Muhammad Harits Hudzaifah Pohan; Najwa Azizah Husnan Tengku; Nurazizah Dawamah; Sindy Nurhaliza; Sri Nurhalijah; Tasya Rahmatika Basitu; Zaki Fadhillah (PT. Alahyan Publisher Sukabumi, 2025)
The common problem that occurs in education is the failure to achieve educational goals. This problem also occurs in Arabic language learning caused by the lack of utilization and lack of improvisation of strategies in the learning process. The existing strategy seems menotonous and results in a lack of student interest in Arabic. For this reason, it is necessary to have a strategy in learning in order to increase the impetus for learning so that it can improve cognitive and intellectual abilities. The aspect of tawhid is the belief in God without associating it. This principle is the main purpose of the teachings brought by the Prophet Muhammad SAW. This research aims to find out the methods and strategies in Tawhid-based Arabic language learning. The results of the research conducted show that the need for a special strategy in instilling the value of tawhid through Arabic language learning. This is an effort to provide an understanding that everything in this world is related to Allah SWT, including in the field of education. And so that students can have good morals and manners in everyday life because they always feel watched by God the creator.